Handbook of Research on Estimation and Control Techniques in E-Learning Systems - Mkrttchian V. Vardan; Bershadsky A. Alexander; Bozhday A. Alexander; Kataev M. Yu. Mikhail Yurievich; Kataev S. Sergey (IGI Global, 2015)
Title screen